2013
DOI: 10.1007/s10585-013-9628-z
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of ΔNp63 downregulation in the invasion and metastasis of oral squamous cell carcinoma via induction of a mesenchymal phenotype

Abstract: Epithelial-to-mesenchymal transition (EMT), an essential developmental program, is involved in tumor progression. ΔNp63, a homolog of p53, is associated with the EMT program, but the detailed mechanism remains to be elucidated. In this study, we investigated the role of ΔNp63 in EMT during progression of oral squamous cell carcinoma (OSCC). Five OSCC cell lines and specimens from 78 patients with OSCC were used. The expressions of ΔNp63, p63α, p63β and epithelial markers (cytokeratins 5 and 14) was detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…In our previous study, we showed that down‐regulated vimentin and down‐regulated E‐cadherin expression was found in the oral cancer cells at the invasive front. Interestingly, the vimentin positive rate or the presence of decreased intensity of ΔNp63 was positively associated with the frequencies of metastases and poor prognosis in the OSCC patients (Goto et al, ). These results indicated that ΔNp63 down‐regulation in cancer cells is associated with mesenchymal phenotype in tumor progression of OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, we showed that down‐regulated vimentin and down‐regulated E‐cadherin expression was found in the oral cancer cells at the invasive front. Interestingly, the vimentin positive rate or the presence of decreased intensity of ΔNp63 was positively associated with the frequencies of metastases and poor prognosis in the OSCC patients (Goto et al, ). These results indicated that ΔNp63 down‐regulation in cancer cells is associated with mesenchymal phenotype in tumor progression of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…SQUU‐B cells show histologically invasive growth and have high metastatic potential (86.7% incidence of cervical lymph node metastasis), whereas SQUU‐A cells demonstrate expansive growth and have low metastatic ability (Morifuji, Taniguchi, Sakai, Nakabeppu, & Ohishi, ). SQUU‐BO cells were generated by transfection with ΔNp63β expression vector, as previously described (Goto et al, ). All cell lines were maintained in a humidified atmosphere of 5% CO 2 at 37 °C, and cultured in Dulbecco's modified Eagle's medium (DMEM)/F‐12 (Life Technologies, Carlsbad, CA) supplemented with 10% fetal bovine serum (FBS) and 100 units/ml penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations